M-Pesa and mobile money in Kenya : pricing for success - Markovich, Sarit, (SAGE knowledge. Cases., 2016)
The Kenyan government's announcement of a new 10% tax in March 2013 threatened the future prospects of M-Pesa, Safaricom's mobile money transfer service, which had revolutionized the way money moved in Kenya. The new tax would be levied on all cash transfers but was largely targeted at M-Pesa, which controlled around 80% of the cash transfer market. In response to the new tax, Safaricom, the mobile communications market leader, announced a 10% price increase. This case presents the structure Safaricom established in order to develop a mobile money transfer service in Kenya.